Penerapan Model Discovery learning dan Strategi Bowling Kampus Untuk Meningkatkan Hasil Belajar Kognitif dan Motivasi Belajar IPA Siswa Kelas VII A di SMP Kristen 2 Salatiga Pada Materi Energi - Yuliani, Mia; Keliat, Natalia Rosa; Sastrodihardjo, Santoso; Kurniawati, Dewi (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
ABSTRACTThe purpose of this study is to improve the cognitive learning results and students’ learning motivation through the discovery learning model and bowling campus strategy, as well as applying the discovery learning model and bowling campus strategy in the energy material. This study was done in SMP Kristen 2 Salatiga by using the students from Class VII A as the subjects. The study used some instruments such as observation sheets, questionnaires and tests. The descriptive analysis was employed in this study. The results of this study show that the percentage of the students’ cognitive learning results fulfilling the 75 competence standard (KKM) in cycle I is 52,38% and it becomes 85,71% in cycle II. The observation result of the students’ learning motivation in cycle I is 76, 19% students achieving good minimum category and it becomes 100% students achieving good minimum category. Based on the students’ perception data about their motivation, there are 100% students in cycle I and II achieving the good minimum category. The results of applying the discovery learning model and bowling campus strategy are capable to make the students to be more active in the learning process, to improve their motivation during the learning process, to facilitate them to comprehend the material concept and to review the materials in order to improve their cognitive learning results. Keywords: Discovery Learning, Bowling Campus Strategy, Learning and Motivation Results